Can pretreatment lactate dehydrogenase to albumin ratio predict pathological complete response after neoadjuvant chemotherapy in breast cancer patients? - Savaş, Gözde; Günel, Nazan; Özet, Ahmet (Journal of Medical Biochemistry, 2025)
Background: The aim of this study is to evaluate the predictive significance of platelet lymphocyte ratio (PLR), neutrophil lymphocyte ratio (NLR), lymphocyte monocyte ratio (LMR), systemic immune-inflammation (SII), prognostic nutritional index (PNI), The hemoglobin, albumin, lymphocyte, and platelet (HALP) score and lactate dehydrogenase to albumin ratio (LAR) for pCR in breast cancer with neoadjuvant chemotherapy (NACT).Methods: A total of 121 patients who received NACT between February 2012 and November 2021 were included. LAR, NLR, PLR, MLR, SII, PNI and HALP were calculated according to formulas. The cut-off value for markers were obtained by Receiver operating characteristic curve (ROC) analyses. Independent predictive factors for pCR were determined using multivariate regression analysis. Results:  The pCR rate was achieved in 31.4% of patients. Median values of NLR, PLR, MLR, SII, PNI and HALP were similar in pCR (+) and pCR (-) (p > 0.05). Median LAR value was significantly higher in pCR (+) than pCR (-) (50.80 vs 42.62, respectively (p=0.002)). The optimal cutoff value of LAR was 46.27. Multivariate analysis showed that LAR ³46.27 and HER-2 positivity were the independent predictive factors for pCR [OR = 2.851 (95% CI = 1.142-7.119, P = .025), OR = 3.431 (95% CI = 1.163-10.123, P = 0.026), respectively].Conclusion: LAR is a simple, inexpensive, and convenient method for predicting pCR in breast cancer with NACT.
Keywords: LAR; LDH; albumin; neoadjuvant chemotherapy; breast cancer; complete response